Pengaruh Model Pembelajaran Planning, Attention, Simultaneous, and Successive Processing (PASS) terhadap Keterampilan Membaca Permulaan Siswa Kelas II SDN 21 Lubuk Lintah - Feny Febiola; Sry Apfani; Alfroki Martha (Lembaga Yasin AlSys, 2025)
The low level of early reading skills among second-grade students at SDN 21 Lubuk Lintah serves as the background of this study, as it directly impacts both the learning process and the development of students’ foundational literacy. This research aims to examine the effect of the Planning, Attention, Simultaneous and Successive Processing (PASS) learning model on early reading skills among second-grade students. The research employed a pre-experimental design with a one-group pretest–posttest approach. The population and sample consisted of all 28 students in Class II.3. Data were collected through an early reading test administered before and after the implementation of the PASS model. Results showed that students’ early reading skills were in the